Approaches for Ending Ineffective Programs: Strategies From State Public Health Practitioners - Rodriguez Weno, Emily; Allen, Peg; Mazzucca, Stephanie; Farah Saliba, Louise; Padek, Margaret; Moreland-Russell, Sarah; Brownson, Ross C. (Frontiers in Public Health, 2021)
Background: Public health agencies are increasingly concerned with ensuring they are maximizing limited resources by delivering evidence-based programs to enhance population-level chronic disease outcomes. Yet, there is little guidance on how to end ineffective programs that continue in communities. The purpose of this analysis is to identify what strategies public health practitioners perceive to be effective in de-implementing, or reducing the use of, ineffective programs. Methods: From March to July 2019, eight states were selected to participate in qualitative interviews from our previous national survey of US state health department (SHD) chronic disease practitioners on program decision making. This analysis examined responses to a question about “…advice for others who want to end an ineffective program.” Forty-four SHD employees were interviewed via phone. Interviews were audio-recorded, and the conversations were transcribed verbatim. All transcripts were consensus coded, and themes were identified and summarized. Results: Participants were program managers or section directors who had on average worked 11 years at their agency and 15 years in public health. SHD employees provided several strategies they perceived as effective for de-implementation. The major themes were: (1) collect and rely on evaluation data; (2) consider if any of the programs can be saved; (3) transparently communicate and discuss program adjustments; (4) be tactful and respectful of partner relationships; (5) communicate in a way that is meaningful to your audience. Conclusions: This analysis provides insight into how SHD practitioners recommend de-implementing ineffective programs. Systematic assessment of strategies to end ineffective programs could further the understanding of de-implementation and its effect on state-level public health programming.